Bibliometric Analysis: The Urgency Of Metacognitive Optimization For Early Childhood - Iklimatul Hasanah; Arin Auliani Hamel; RR Deni Widjayatri (Universitas Panca Sakti Bekasi, 2024)
Metacognition for early childhood is crucial for optimization. The aim of this research is to optimize metacognition in young children aged 0-8 years. The subjects in this study are young children within the age range mentioned. The research employs the Systematic Literature Review (SLR) method and bibliometric analysis. Data sources include Google Scholar spanning from 2018 to 2023, Harzing’s Publish or Perish (Pop), and VOSviewer, resulting in 20 articles. The findings reveal that metacognition in early childhood comprises 11 clusters: Cluster 1 in red, Cluster 2 in dark green, Cluster 3 in dark blue, Cluster 4 in yellow, Cluster 5 in purple, Cluster 6 in light blue, Cluster 7 in orange, Cluster 8 in brown, Cluster 9 in pink, Cluster 10 in cream, and Cluster 11 in light green. The optimization of metacognition in young children can be achieved through storytelling, planning, evaluation, discussing the results of their work, and parental motivation.